Acoustic analysis of prosody in Sydenham's chorea Análise acústica da prosódia em coréia de Sydenham - Patrícia M Oliveira; Francisco Cardoso; Débora P Maia; Mauro César Q Cunningham; Antonio Lúcio Teixeira Jr; César Reis (Arquivos de Neuro-Psiquiatria)
There are few studies of language and speech in patients with Sydenham's chorea (SC). We have done an acoustic analysis of fundamental frequency (F0), duration and intensity of declarative and interrogative sentences made by 20 SC patients, 20 patients with rheumatic fever (RF) without chorea, and compared them with 20 healthy age-matched controls (CO). Each group included 12 females. We found that there is no difference between the RF and CO groups in all studied parameters. Patients with SC, however, presented with a speech characterized by decreased F0 range (difference between minimum and maximum F0), shorter duration of sentences, and higher intensity of the first syllable of sentences. The findings were not influenced by the nature of the sentences (i.e. , declarative or interrogative), but for all variables they were significantly more severe in males than females. In conclusion, we have demonstrated that patients with acute SC have an impairment of modulation of F0 and longer duration of emission of sentences, resulting in a monotone and slow speech. This pattern is similar to what has been described in other basal ganglia illnesses, such as Parkinson's disease, Huntington's disease and Wilson's disease. Há poucos estudos sobre linguagem e fala em pacientes com coréia de Sydenham (CS). Fizemos uma análise acústica da freqüência fundamental (F0), duração e intensidade de sentenças declarativas e interrogativas feitas por 20 pacientes com CS, 20 pacientes com febre reumática (FR) sem coréia, comparando-os com 20 controles saudáveis e pareados por idade (CO). Cada grupo incluiu 12 mulheres. Foi encontrado que não há diferença entre os grupos FR e CO quanto a todos parâmetros estudados. Pacientes com CS, contudo, apresentaram-se com fala caracterizada pela redução da variação de F0 (diferença entre F0 mínima e máxima), duração mais curta das sentenças e maior intensidade da primeira sílaba das sentenças. Os achados não foram influenciados pela natureza das sentenças (i.e. , declarativas ou interrogativas), mas os achados foram mais evidentes em todas as variáveis em homens em contraste com mulheres. Em conclusão, demonstramos que pacientes com CS aguda têm prejuízo da modulação da F0 e duração mais longa da emissão de sentenças, resultando em fala mais lenta e monótona. Esse padrão é semelhante ao que tem sido descrito em outras fecções dos núcleos da base, tais como doença de Parkinson, doença de Huntington e doença de Wilson.